Thyrotropin reference interval in older adults - Zhai, Xiaodan; Li, Yongze; Teng, Xiaochun; Teng, Weiping; Shi, Xiaoguang; Shan, Zhongyan (Endocrine Connections, 2025)
It is estimated that by the year 2050, 16% of the world’s population will be 65 years old and above. As the global aging population continues to grow, there is an increasing focus on thyroid disorders among older individuals. Thyrotropin is widely used in diagnosing subclinical thyroid diseases due to its high sensitivity as an indicator of changes in thyroid function. However, thyrotropin levels change with age, and different reference intervals have been proposed in various studies. The variation in thyrotropin ranges among older adults is probably caused by the heterogeneity of the studied population. This review aims to provide an overview of the existing literature on thyrotropin reference intervals in older adults and their distinction as adaptive or pathologic. Recent research indicates that older individuals may have slightly elevated levels of thyrotropin and higher upper limits of reference intervals. Therefore, a higher thyrotropin threshold for diagnosing and treating subclinical hypothyroidism in the elderly seems reasonable.